Contextual Christology A Tribal Perspective - L. H. Lalpekhlua; Donated by Rev Dr Go Van Mung (Delhi ISPCK, 2007)
With reference to Mizoram, India.
Keywords: Christianity -- India -- Mizoram. Jesus Christ -- Person and offices. Mizoram (India) -- Religion. Jesus Christ. Christianity. Christology. Religion. India -- Mizoram